Malacoraja obscura, Brazilian Soft Skate - Pollom, R. (2020)
The Brazilian Soft Skate (Malacoraja obscura) is a small (to 68 cm total length) skate that has a very restricted range in the Southwest Atlantic Ocean from central Espírito Santo and northern Rio de Janeiro states in Brazil. It inhabits the continental slope at depths of 808-1,105 m. Although Extent of Occurrence cannot be calculated because the species is only known from two localities, it is suspected to be about 30,000 km2 (if the species is assumed to inhabit the steep slope between the two known localities). Area of Occupancy is estimated at 3,680 km2 (calculated based on including the known depth range of the species between the two known localities). This skate inhabits waters currently beyond the reach of fisheries, and there are no other known threats. Therefore, the population is suspected to be stable and the Brazilian Soft Skate is assessed as Least Concern.